Microbial and Biochemical Biofungicides Ineffective Against Alternaria Black Spot on Organic Kale - Anthony P. Keinath (PhytoFrontiers)
In South Carolina, the disease black spot on kale is caused by the fungi Alternaria brassicicola and A. japonica. Because all kale cultivars are presumed to be susceptible, organic producers may apply biofungicides to prevent or manage black spot. Microbial and biochemical biofungicides were tested in the greenhouse (12 products) and the field (10 products) against black spot caused by both Alternaria spp. on organically produced kale. Thereafter, three biofungicides (copper hydroxide, potassium silicate, and Reynoutria sachalinensis extract) were tested in the field on three kale cultivars. Although several biofungicides reduced black spot in the greenhouse compared with the water-treated control, no biofungicides did so in the field even though they were applied preventatively before plants were inoculated. Biofungicides also did not increase the weight of healthy leaves compared with the water-treated control in any field experiment. Conversely, two biofungicides that increased the severity and incidence of black spot in the greenhouse, B. amyloliquefaciens F727 and potassium bicarbonate, reduced weights of healthy leaves in the field. On average, curly kale cultivar Winterbor had fewer diseased leaves than curly kale cultivar Darkibor, and lacinato kale cultivar Toscano had fewer diseased leaves than curly kale. Winterbor also consistently produced greater healthy leaf weight than Darkibor. Biopesticides are not recommended against black spot on organic kale. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.